2018
DOI: 10.1039/c8fo01495g
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the tropomyosin structure alter the angiotensin-converting enzyme inhibitory activity and texture profiles of eel balls under high hydrostatic pressure

Abstract: Changes in the structure of tropomyosin (TM) altered the texture profiles of eel balls and the inhibitory activity of the angiotensin-converting enzyme (ACE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…With increasing pressure, the hardness, springiness and chewiness values of red swamp crayfish (Procambarus clarkia) initially increased sharply, then decreased slightly, but all were higher than those of the control [82]. In our work, the texture parameters including hardness, springiness, chewiness and cohesiveness of eel balls were significantly improved with HHP treatment, and the optimum treating pressure was 400 MPa [9,36]. As for the eel surimi, the hardness, chewiness, gel strength and water-holding capacity increased significantly as well under HHP treatment, while the viscosity decreased [9,36].…”
Section: Effect Of Hhp On Meat Qualitymentioning
confidence: 52%
See 4 more Smart Citations
“…With increasing pressure, the hardness, springiness and chewiness values of red swamp crayfish (Procambarus clarkia) initially increased sharply, then decreased slightly, but all were higher than those of the control [82]. In our work, the texture parameters including hardness, springiness, chewiness and cohesiveness of eel balls were significantly improved with HHP treatment, and the optimum treating pressure was 400 MPa [9,36]. As for the eel surimi, the hardness, chewiness, gel strength and water-holding capacity increased significantly as well under HHP treatment, while the viscosity decreased [9,36].…”
Section: Effect Of Hhp On Meat Qualitymentioning
confidence: 52%
“…The hardness, elasticity, mastic ability and cohesiveness increased by 3.00, 1.61, 5.96 and 1.23 times, respectively, when treated at 400 MPa for 15 min. In our work [9,36], further exploration of the protein structure revealed that the texture parameters of eel products were negatively correlated with the α-helix and β-sheet of proteins, but positively correlated with the random coil and β-turn of proteins (Figure 3). These results indicated that food textures can be directly related to the secondary and tertiary structures of MP.…”
Section: Effect Of Hhp On Meat Qualitymentioning
confidence: 61%
See 3 more Smart Citations